PREVALENCE OF IMPACTED MAXILLARY CANINES IN PATIENTS REPORTING TO A DENTAL HOSPITAL-A RETROSPECTIVE STUDY (Journal of Pharmaceutical Negative Results, 2022)
A tooth is considered impacted when its eruption is hampered by other teeth, bone, or soft tissues. Diagnosis is generally based on clinical and radiological analyses.It can affect the patient’s self confidence and alter the functions. This study is important to plan intervention programs and highlight the importance of early orthodontic screening.The aim of the study is to determine the prevalence of impacted canine in patients reporting to saveetha dental college.A total of 86,000 records of patients were reviewed . Data was collected and a retrospective study was done. Overall case sheets were reviewed which were dated between june 2019 to march 2020. Retrospective data of patients who visited the Department of Orthodontics was analysed. 14 patients who fulfilled the inclusion and exclusion criteria were included. The data was collected in excel sheets by the patient records of saveetha dental college and hospital and subjected study was performed followed by data analysis using SPSS and the variables were defined. It was observed that the impaction of maxillary canine was predominant in male patients when compared to that of femalepatients(Pearson’s Chi square value = 1.167; df =1; p-value: 0.280 (p>0.05); hence statistically not significant) in the age group of 11-20 years(Pearson’s Chi square value=0.729; df=2; p-value: 0.694 (p>0.05); hence statistically not significant) and it was most commonly found in the second Quadrant